2021
DOI: 10.3389/fneur.2021.659678
|View full text |Cite
|
Sign up to set email alerts
|

Silybin Alleviates Experimental Autoimmune Encephalomyelitis by Suppressing Dendritic Cell Activation and Th17 Cell Differentiation

Abstract: Silybin, a peculiar flavonoid compound derived from the fruit and seeds of Silybum marianum, exhibits strong anti-inflammatory activities. In the present study, we found that silybin effectively alleviated experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), via inhibition of dendritic cell (DC) activation and Th17 cell differentiation. Silybin treatment greatly ameliorated the disease severity and significantly declined inflammation and demyelination of the central nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In IFN-ß-treated multiple sclerosis patients, SM was demonstrated to suppress Th1 proliferating activity associated with the inhibition of T-bet gene expression and IFN-γ production by the immune cells [155]. In an animal model of multiple sclerosis, SB was illustrated to decrease DC activation and to suppress pathogenic Th17 inflammatory cell responses, significantly attenuating inflammation and demyelination of the central nervous system in experimental mice [156]. Importantly, SM treatment was found to mitigate virus-induced increased pro-inflammatory cytokine production and liver inflammation in a mouse model of Mayaro virus infection [157].…”
Section: Other In Vivo Model Systems and Disease Statesmentioning
confidence: 99%
“…In IFN-ß-treated multiple sclerosis patients, SM was demonstrated to suppress Th1 proliferating activity associated with the inhibition of T-bet gene expression and IFN-γ production by the immune cells [155]. In an animal model of multiple sclerosis, SB was illustrated to decrease DC activation and to suppress pathogenic Th17 inflammatory cell responses, significantly attenuating inflammation and demyelination of the central nervous system in experimental mice [156]. Importantly, SM treatment was found to mitigate virus-induced increased pro-inflammatory cytokine production and liver inflammation in a mouse model of Mayaro virus infection [157].…”
Section: Other In Vivo Model Systems and Disease Statesmentioning
confidence: 99%
“…Silybin reduced also the expression of costimulatory molecules (e.g., CD80 and CD86) and MHC II in bone marrow-derived DCs (BM-DCs). 92…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…In agreement with these studies, we previously showed that Silibinin upregulates ERβ expression, induces apoptosis, inhibits proliferation, and reduces expression of the pro-inflammatory cytokines through ERβ binding in T lymphocytes from female and male healthy donors and patients with active Rheumatoid Arthritis [ 10 ]. Moreover, Silibinin has been also shown immunosuppressive effects in experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis via inhibition of dendritic cell (DC) activation, and Th17 cell differentiation [ 11 ]. Silibinin has also been demonstrated to inhibit phenotypic and functional maturation of murine bone marrow-derived DC and Th1 polarization.…”
Section: Introductionmentioning
confidence: 99%